Prevalence and Manifestations of Dental Ankylosis in Primary Molars Using Panoramic X-rays: A Cross-Sectional Study - Daniela Eşian; Cristina Ioana Bica; Oana Elena Stoica; Timea Dako; Alexandru Vlasa; Eugen Silviu Bud; Denisa Salcudean; Liana Beresescu (MDPI AG, 2022)
Dental ankylosis is a serious condition defined as the process that causes the fusion between the dentin or the cementum of the root and the alveolar bone, with the obliteration of the periodontal ligament becoming progressively replaced by bone tissue. The aim of the study was to determine the prevalence, location, severity, and association of dental ankylosis in primary molars with other dental anomalies such as the agenesis of permanent buds. For this study 150 panoramic x-rays were selected from patients with temporary or mixed dentition, aged six to twelve years old, from a private dentistry office and from the Pediatric Dentistry Department of UMFST in Targu-Mures, Romania. In order to identify the cases with dental ankylosis, the presence and severity of the infraocclusion, displacements of the neighboring teeth, the appearance of the root area, and the relationship with the bone tissue were examined. For evaluation of the categorical data we used Fischer's exact test and the Chi-squared test and the chosen significance level was set at 0.05. The results showed that the highest percentage of cases with ankylosis was found in the first group (six to nine years old), respectively, with 72% of cases compared with the second group (ten to twelve years old) with 28% of cases. Findings showed that there was no positive association between dental ankylosis and gender, but a strong correlation was found regarding the location on the dental arches. Most cases were identified on the lower arch with a higher percentage in quadrant three. Of the two primary molars, the most affected by ankylosis was the first molar in quadrant three, followed by the second molar, and finally the first molar in quadrant four. Most cases diagnosed with ankylosis had a mild to moderate degree of infraocclusion; therefore, changes in the functional balance of the dental arch and on neighboring teeth were insignificant. There were some differences obtained between our results and studies from the literature, especially regarding the localization in the lower left dental arch, but these differences can be attributed to the number of the subjects selected and from the methodology of dental ankylosis diagnosis. Based on the data obtained, it was concluded that ankylosis is a dental condition which occurs in children in early mixed dentition, especially in the lower arch, with the first primary molar being the most affected tooth. The presence of infraocclusion and the absence of dental mobility, especially during the stage of primary molars' root resorption, are the main signs which must be followed to make an early diagnosis and prevent further complications.